Serum levels and gene polymorphisms of angiopoietin 2 in systemic lupus erythematosus patients - Jia-Min Wang (Nature Portfolio, 2021)
Abstract This study aimed to discuss association between serum Angiopoietin2 (Ang2) levels, Ang2 gene polymorphisms and systemic lupus erythematosus (SLE) susceptibility. It was carried out by 235 SLE, 342 other inflammatory autoimmune diseases patients and 380 healthy individuals. Serum Ang2 levels was examinated by ELISA, and Ang2 rs12674822, rs1823375, rs1868554, rs2442598, rs3739390 and rs734701 polymorphisms were genotyped using KASP. Increased Ang2 concentrations in SLE patients were observed compared with healthy controls and patients with other inflammatory autoimmune diseases. For allelic contrast, except for rs1823375 (P = 0.058) and rs2442598 (P = 0.523), frequencies of alleles for other polymorphisms were significantly different between SLE patients and controls. Genotypes for rs12674822 (TT), rs1868554 (TT, TA and TT+TA), rs734701 (TT) were negatively correlated with SLE susceptibility (OR = 0.564 for rs12674822; OR = 0.572, OR = 0.625, OR = 0.607 for rs1868554; OR = 0.580 for rs734701). Patients carrying rs1868554 T allele and rs3739390 G allele were more likely to develop hematuria (P = 0.039; P = 0.003). The G allele frequencies of rs12674822 and rs2442598 were higher in SLE patients with proteinuria (P = 0.043; P = 0.043). GC genotype frequency of rs3739390 was higher in patients with ds-DNA (+) (P = 0.024). In summary, SLE had increased serum Ang2, which may be a potential biomarker, and the polymorphisms correlated with SLE.